2019
DOI: 10.22201/fpsi.20074719e.2019.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy Development: Gender and Age Differences from Adolescence to Emerging Adulthood

Abstract: The development of autonomy during the transition to adulthood may present itself in different forms, depending on age, gender and cultural variations. Grounded in developmental psychology, this study examined gender and age differences in autonomy in Brazilian youth. Participants were 154 Brazilian adolescents and emerging adults (14-33 years old, M= 20.87, SD= 3.74, 50% female) from the state capital of Rio de Janeiro. Our findings indicate a positive association between age and autonomy scores in the Kağitç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…Research results are more coherent when it comes to age. Several studies (Graça et al, 2010;Dutra-Thomé et al, 2019) point out that older adolescents exhibit better levels of autonomy, as expected.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Research results are more coherent when it comes to age. Several studies (Graça et al, 2010;Dutra-Thomé et al, 2019) point out that older adolescents exhibit better levels of autonomy, as expected.…”
Section: Introductionsupporting
confidence: 60%
“…When focusing on gender differences, those variances are nowadays less important than they were in the past. In fact, male and female show autonomous behaviors at different stages of their adolescence, however, this gender equality is not evident in all cultural contexts (Dutra-Thomé et al, 2019). It should also be noted that the studies conducted so far are not yet able to provide a consensus on the relevance of this variable in autonomy development.…”
Section: Introductionmentioning
confidence: 95%
“…According to Glynn and Mayock (2019) and Isakov and Hrnčić (2018), the strength of a young person's family environment translates into differences in their psychological well-being; hence the need to develop interventions specifically designed to provide stability during people's transition to adulthood. Similarly, authors such as Fousiani et al (2014); Liga et al (2017), Schofield et al (2017), andDutra-Thomé et al (2019) consider that the possibility of achieving autonomy and independence is shaped by certain contextual variables that affect the configuration of the expectations forged by each individual throughout their life; this requires assessing whether the lack of equality during this transition has any effect on the way in which people decide on their longterm goals. Further analysis of the dimensions measured by the EDATVA showed that the Colombian sample presented higher scores in the critical capacity and self-organization dimensions, and the mean scores of the context analysis and sociopolitical involvement dimensions were very similar for both samples.…”
Section: Discussionmentioning
confidence: 99%
“…These factors will influence with greater or lesser intensity depending on the environment studied, which could explain the differences observed in the level of autonomy between Spanish and Colombian youth, in addition to interacting with individual barriers that reduce the subject's ability to access autonomy within of the same analysis scenario (Brim et al, 2019). In addition, it should be borne in mind that the knowledge about the problems individuals face in achieving their autonomy is limited, despite the indirect relevance of these on psychological well-being (Dutra-Thomé et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation